PERLAKUAN PERKERASAN HOT MIX ASPAL MENGGUNAKAN LATEK TERHADAP DEFORMASI PERMANEN AKIBAT BEBAN BERULANG - Nurani, Puri (FSTPT Indonesia, 2015)
Hot Mix Asphalt (HMA) is a Flexible Pavement which has been frequently used as it can be got in with ease. Never the less, the increasing number of passing, vehicles results in premature damage due to overloading. A long term objective of this research is to decrease the premature damage by adding some latex to the pavement mixture of aggregate and asphalt. While its specific objective is to add some latex to HMA pavement mixture to detect the effect of fatigue which can be seen through permanent deformation and rutting. Having added some latex, it can be detected how serious the damage of the pavement will be. Experimental method was employed by using Bina Marga standardized aggregate, 4,5% - 6% latex addition to petroleum asphalt penetration 60/70 had to go thorugh Beam Apparatus Pavement Test. While Wheel Tracking Machine (WTM) was applied to test, rutting. The analyses of 4,5%- 6% latex addition to Maximum Asphalt Content result in 2,43 mm and 2,66mm deformation It is suggested to carry out a research into the effect of 7% and 8%latex addition to Maximum Asphalt Content.